THE IMPACT OF SOCIAL CHANGE ON ACCESS TO EDUCATION IN LACKGROUND AREAS - Karmelia, Arina; Muti’ah, Eva (Bina Bangsa International Journal of Business and Management, 2025)
The aim of this research is to describe the impact of social change on access to education in disadvantaged areas using a literature approach. The method used is a descriptive method with a literature approach, by analyzing 50 international and national journals that have been published online. With a time, frame of 5 years, 2021-2025. This research aims to describe the impact of social change on access to education in disadvantaged areas through a comprehensive literature study approach. Social changes covering demographic, economic, technological and cultural aspects are analyzed based on various relevant literature sources to identify their influence on the availability, affordability and quality of education in areas classified as underdeveloped. This research summarizes and synthesizes findings from various studies, reports and scientific articles to provide a clear picture of the challenges and opportunities that arise as a result of social change in the context of access to education in underdeveloped areas.